Impact of Digitalization in Business World - Magdalena Alina ILCUS (Revista de Management Comparat International)
Digitalization is in every field of our lives: education and schools, social networking, in business, as almost each company has a website and in business processes: marketplaces, logistics, and more and more, in accounting. Consequently, the current age became “digital era”. Digital technology allows making tasks faster and more accurate. That’s why, its growth impacts digital marketplace and continues to grow each and every year: Amazon, Alibaba, Ebay, Emag, Olx. Digital networking is developing fast too: Facebook, Instagram, Twitter, Pinterest, LinkedIn. This article focuses on being digital issue in the business world by presenting some of its advantages and why it is important going digital for companies.